Optimization in the Real World Toward Solving Real-World Optimization Problems - Fujisawa, Katsuki; Shinano, Yuji.; Waki, Hayato; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book clearly shows the importance, usefulness, and powerfulness of current optimization technologies, in particular, mixed-integer programming and its remarkable applications. It is intended to be the definitive study of state-of-the-art optimization technologies for students, academic researchers, and non-professionals in industry. The chapters of this book are based on a collection of selected and extended papers from the  "IMI Workshop on Optimization in the Real World" held in October 2014 in Japan.
Advanced Computing & Optimization Infrastructure for Extremely Large-Scale Graphs on Post Peta-Scale Supercomputers -- ppOpen-HPC: Open Source Infrastructure for Development andExecution of Large-Scale Scientific Applications on Post-Peta-Scale Supercomputers with Automatic Tuning (AT) -- Structure-based Primal Heuristics for Mixed Integer Programming -- Optimal Turbine Allocation for Offshore and Onshore Wind Farms -- Optimal Cycles for Persistent Homology via Linear Programming -- Optimal Battery Control for Smart Grid Nodes -- Pre-operative activities and Operating Theater planning in Emilia-Romagna, Italy -- Recent Issues in International Supply Chain Network Design - Economic Partnership Modeling -- MILP Approaches to Optimal Design and Operation of Distributed Energy Systems -- Demand Response Optimization Based on Building's Characteristics.
Keywords: Engineering mathematics; Engineering -- Data processing; Mathematical optimization; Calculus of variations; Operations research; Mathematical and Computational Engineering Applications; Calculus of Variations and Optimization; Operations Research and Decision Theory